Replacement of filters for respirable quartz measurement in coal mine dust by infrared spectroscopy. Issue 2 (1st February 2016) - Farcas, Daniel; Lee, Taekhee; Chisholm, William P.; Soo, Jhy-Charm; Harper, Martin
ABSTRACT: The objective of this article is to compare and characterize nylon, polypropylene (PP), and polyvinyl chloride (PVC) membrane filters that might be used to replace the vinyl/acrylic co-polymer (DM-450) filter currently used in the Mine Safety and Health Administration (MSHA) P-7 method (Quartz Analytical Method) and the National Institute for Occupational Safety and Health (NIOSH) Manual of Analytical Methods 7603 method (QUARTZ in coal mine dust, by IR re-deposition). This effort is necessary because the DM-450 filters are no longer commercially available. There is an impending shortage of DM-450 filters. For example, the MSHA Pittsburgh laboratory alone analyzes annually approximately 15, 000 samples according to the MSHA P-7 method that requires DM-450 filters. Membrane filters suitable for on-filter analysis should have high infrared (IR) transmittance in the spectral region 600–1000 cm −1 . Nylon (47 mm, 0.45 µm pore size), PP (47 mm, 0.45 µm pore size), and PVC (47 mm, 5 µm pore size) filters meet this specification. Limits of detection and limits of quantification were determined from Fourier transform infrared spectroscopy (FTIR) measurements of blank filters. The average measured quartz mass and coefficient of variation were determined from test filters spiked with respirable α-quartz following MSHA P-7 and NIOSH 7603 methods. Quartz was also quantified in samples of respirable coal dust on each test filter type using the MSHA and NIOSH analysis methods. The results indicate that PP and PVC filters may replace the DM-450 filters for quartz measurement in coal dust by FTIR. PVC filters of 5 µm pore size seemed to be suitable replacement although their ability to retain small particulates should be checked by further experiment.